Język wypowiedzi publicznych Donalda Tuska w latach 2005-2007 - Grzesiński, Damian (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
There is a special model of liberal language in political science which has certain features: a tendency to use special lingual terms, tolerance, political correctness, faith in its beliefs, sense of responsibility for the country and an exposure of liberal values such as freedom and latitude, etc. The other thing is that Donald Tusk has also certain lingual features which partly fit to the liberal language model and remain a constant feature of Tusk’s language. The main features of his language are: exposure of freedom as a value constantly in danger, extraordinary underlining the role of intellect, search for confirmation of what he says to the audience, sense of responsibility for the country, comparing politics to the world of football.